Detection and Sequence Analysis of Pepper Yellow Leaf Curl Virus Isolates That Infected Chili (Capsicum annuum L.) in Bengkulu, Indonesia - Gustian, Deri; Sutrawati, Mimi; Fauzi, Ariffatchur; Hamidi, Ilmi; Mengesha, Nakachew Minuye; Do, Duy-Hung; RATTANA, Nitchayamon (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
Pepper yellow leaf curl Aceh virus (PepYLCAV) and pepper yellow leaf curl Indonesia virus (PepYLCIV) are begomoviruses that dominate chili cultivation in Indonesia. Characterization of these two begomoviruses is essential as basic information for the development of virus control technologies. The symptoms on chili plants indicate that PepYLCIV is more severe than PepYLCAV, with severe mosaic, curling, and yellowing, whereas PepYLCAV causes only mild mosaic and yellowing. Sequencing results also show that the nucleotides and amino acids between PepYLCAV and PepYLCIV are significantly different. This suggests that the pathogenicity of the two viruses on chili plants differs. Protein structure predictions using AlphaFold3 also show significant differences. Based on available data, control of PepYLCAV and PepYLCIV can be achieved using different approaches, as these viruses have distinct sequences that may affect their pathogenicity.